2019
DOI: 10.1002/tkm2.1226
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of yokukansan on behavioral and psychological symptoms of dementia

Abstract: Background Cognitive dysfunction is often accompanied by behavioral and psychological symptoms of dementia (BPSD) in patients with Alzheimer's disease and other forms of senile dementia. BPSD include agitation, aggression, and hallucinations. BPSD have a serious effect on the quality of life of dementia patients and their caregivers, but effective drug therapy for BPSD has not been identified as yet. Typical and atypical antipsychotics that are used for the treatment of BPSD are known to cause a variety of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…The mechanisms underlying the effects of YKS on these positive symptoms have been extensively examined in cellular, animal, and pharmacokinetic experiments. As reviewed previously [69–72], it has been revealed that YKS modulates many neuronal pathways including serotonergic, glutamatergic, GABAergic, and other neurotransmitter pathways in CNS. The most well‐characterized targets of YKS in treating positive psychiatric symptoms are the serotonergic and glutamatergic pathways.…”
Section: Basic Studies On Yksmentioning
confidence: 99%
“…The mechanisms underlying the effects of YKS on these positive symptoms have been extensively examined in cellular, animal, and pharmacokinetic experiments. As reviewed previously [69–72], it has been revealed that YKS modulates many neuronal pathways including serotonergic, glutamatergic, GABAergic, and other neurotransmitter pathways in CNS. The most well‐characterized targets of YKS in treating positive psychiatric symptoms are the serotonergic and glutamatergic pathways.…”
Section: Basic Studies On Yksmentioning
confidence: 99%